A Theory Model of Digital Currency with Asymmetric Privacy - Tinn, Katrin (Management Science, 2026)
This paper considers introducing asymmetric privacy in the design of central bank digital currencies (CBDC) and digital currencies more generally to preserve the privacy of money spent while keeping the benefits of digital records for money received. It is shown that this feature would help minimize real distortions between consumers, firms, and financiers while enabling tax optimization and better access to external financing. Protecting the privacy of consumers is desirable from a welfare and efficiency standpoint as long as there exist noticeable privacy concerns. Implementing asymmetric privacy is technologically feasible, using, for instance, zero-knowledge proofs or other privacy tools. This paper has been accepted by Lin William Cong for the Virtual Special Issue on Digital Finance. Supplemental Material: The online appendix is available at https://doi.org/10.1287/mnsc.2024.06830 .